Long-term treatment with lasmiditan in patients with migraine: post hoc analysis of treatment patterns and outcomes from the open-label extension of the CENTURION randomized trial - Mika Komori; Akichika Ozeki; Yuka Tanji; Eriko Kamiki; John H. Krege; Lily Qian Li; Shiho Suzuki; Mamoru Shibata; Takao Takeshima (The Journal of Headache and Pain, 2024)
Abstract Background The objective of this analysis was to gain new insights into the patient characteristics and other factors associated with lasmiditan usage and clinical outcomes under conditions resembling the real-world setting. Methods This was a post hoc analysis of data from the 12-month, open-label extension (OLE) of the phase 3, double-blind, randomized, controlled CENTURION trial, which examined the efficacy and safety of lasmiditan as acute treatment across four migraine attacks. Patients completing the main study who treated ≥ 3 attacks could continue in the OLE. The initial lasmiditan dose was 100 mg, with dose adjustments to 50 mg or 200 mg allowed at the investigator’s discretion. Patient and clinical characteristics were summarized by dosing pattern and completion status. Safety was assessed based on adverse event (AE) frequency by number of doses. Results In total, 445 patients treated ≥ 1 migraine attacks with lasmiditan during the OLE, 321 of whom (72.1%) completed the study. Forty-seven percent of patients remained on the 100-mg initial dose during the OLE whereas 20.2% used both 100 mg and 50 mg, 30.6% used both 100 mg and 200 mg, and 6 (1.3%) used multiple dose levels. All dosing patterns were associated with clinical and patient-reported improvement; however, the 100-mg group had the highest proportion of patients reporting improvement in the Patient Global Impression of Change – Migraine Headache Condition (56.5% vs 33.4%–52.2%). In comparison, all three groups that made dose adjustments had higher rates of completion compared to the 100-mg group (72.1%–83.3% vs 68.9%). The frequency of AEs decreased with continued use of lasmiditan. Concomitant triptans and lasmiditan use did not increase AE frequency. Conclusions Based on high persistence and patient satisfaction rates, the 100-mg dose appears optimal for most patients. For those who adjusted dose levels, dose adjustments appeared beneficial to improve efficacy or tolerability, retaining patients on treatment. Collectively, the data suggest that patients who experienced efficacy continued to use lasmiditan regardless of the occurrence or frequency of AEs, and continued use appeared associated with fewer AEs. Trial registration European Union Drug Regulating Authorities Clinical Trials Database (EudraCT): 2018–001661-17; ClinicalTrials.gov: NCT03670810; registration date: September 12, 2018. Graphical Abstract